1998
DOI: 10.1159/000054297
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vasoactive Intestinal Peptide and 5-HT<sub>2</sub> Receptor Subtype in Serotonin Stimulation of Basal and Thyrotropin-Releasing-Hormone- Induced Prolactin Release in vitro from Rat Pituitary Cells

Abstract: We have previously demonstrated that 5-HT stimulates not only basal but also thyrotropin-releasing-hormone (TRH)-induced prolactin (PRL) release by acting directly at the pituitary gland level. In the present report, the participation of an autoparacrine action of VIP in the stimulatory effects of 5-HT and the involvement of the 5-HT2 receptor type in mediating serotonin-induced PRL release have been examined. Cultured anterior pituitary cells from ovariectomized adult rats were incubated for 1 h in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Those GnRH neurons in cultures released GnRH into the medium in a pulsatile fashion at a mean interpulse interval of 47 min, which was very similar to that observed in ovariectomized rhesus monkeys in vivo [27, 28, 29]. Furthermore, the immortalized mouse GnRH neurons, the GT1-1 and GT1-7 neurons, were found to release GnRH in a pulsatile fashion with a mean interpulse interval of 36 min [9]or about 25 min [8, 30], similar to the interval reported for LH in castrated male mice in vivo, 28 min [31]. Altogether, these characteristics of cultured GnRH neurons seem to indicate that the GnRH pulse generator may reside within the GnRH neuron itself or the network of GnRH neurons and that inputs from other neurons are not needed to maintain the intermittent releasing activity.…”
Section: Discussionsupporting
confidence: 71%
“…Those GnRH neurons in cultures released GnRH into the medium in a pulsatile fashion at a mean interpulse interval of 47 min, which was very similar to that observed in ovariectomized rhesus monkeys in vivo [27, 28, 29]. Furthermore, the immortalized mouse GnRH neurons, the GT1-1 and GT1-7 neurons, were found to release GnRH in a pulsatile fashion with a mean interpulse interval of 36 min [9]or about 25 min [8, 30], similar to the interval reported for LH in castrated male mice in vivo, 28 min [31]. Altogether, these characteristics of cultured GnRH neurons seem to indicate that the GnRH pulse generator may reside within the GnRH neuron itself or the network of GnRH neurons and that inputs from other neurons are not needed to maintain the intermittent releasing activity.…”
Section: Discussionsupporting
confidence: 71%
“…Physiological control of PRL secretion induced by 5‐HT is mediated, at least in part, by hypothalamic VIP release into the hypophysial portal blood in the rat . VIP antagonist ([D,4‐Cl‐Ph6,Leu17]VIP) partially inhibits the release of PRL induced by 5‐HT, comprising the basal and thyrotrophin‐releasing‐hormone‐stimulated releases . VIP increased 24 hours after DES treatment only in male rats (Table ), which suggests that the increase in PRL after 48 hours might be dependent on the increase in VIP.…”
Section: Discussionmentioning
confidence: 96%
“…At least three physiologically active substances play a role in promoting PRL release from pituitary cells: TRH, vasoactive intestinal polypeptide (VIP) and serotonin (also known as 5-HT) (Apfelbaum 1998). However, 5-HT stimulates PRL secretion through a complex, multi-level action on both the hypothalamus and the pituitary gland (Jørgensen 2007;Fitzgerald and Dinan 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, later studies showed that stimulation of HTR2 affects PRL release by acting directly at the pituitary gland level (Meltzer et al 1983;Apfelbaum 1987;Balsa et al 1998). Stimulation of HTR2 not only promoted PRL release via the local autoparacrine action of VIP, but also directly by activating HTR2s on lactotrophs (Apfelbaum 1998 Souza (1986) described the presence of 5-HT2 binding sites in all three lobes of the rat pituitary gland. However, the density in the anterior lobe was much lower than the density in the intermediate and posterior lobes.…”
Section: Introductionmentioning
confidence: 99%